Keeping the Faith: Filipino Catholic Responses to the Covid-19 Pandemic - Nestor T. Castro (UNHI PRESS, 2022)
Since March 2020, Metro Manila and other places in the Philippines has been on lockdownbecause of the surge of Covid-19 cases in the country. Even churches and other places ofworship have been off-limits to church goers during strict lockdown measures called “EnhancedCommunity Quarantine.” This paper looks at how Filipino Catholics practice their religiousobligations during the pandemic. Since majority (81%) of Filipinos are Roman Catholics, thefocus of this paper is how Filipino Catholics view the Covid-19 pandemic and how they copewith it. The data for this study comes from two sources: 1) interviews with church leaders andlay members; and 2) online and offlne ethnographic observation of religious practices duringthe pandemic. Through an anthropological description of Filipino Catholic attitudes on andresponses to the Covid-19 pandemic, we have a better understanding about Filipino resiliencyin times of crises.